Dinâmica de casais com filhos com transtorno do espectro autista: desafios e impactos na conjugalidade - Gavaldão, Angélica de Lucas (2019)
This is a qualitative research, whose theme is to understand the marital dynamics and challenges experienced by couples who have a child with Autistic Spectrum Disorder (ASD) throughout the Family Life Cycle. Structural Family Therapy was the theoretical approach used to support this study, as well as the concepts of Family Life Cycle and diagnostic guidelines for ASD. The subjects were four couples who had a child with the disorder. The instruments used were the Sociodemographic Questionnaire and the Semi-Structured Interview. The information obtained in the interview was processed by the IRAMUTEQ R software, which mainly assisted in the elaboration of the four categories of analysis: “Category 1 - Different children: impacts on the Family Life Cycle”, gathered the couple's perceptions about the symptoms of ASD and the consequences of their identification on family development. Obstacles are difficult to overcome because they are permeated by families' unpreparedness in dealing with ASD and also the difficulty of dealing with previous idealizations regarding the child; “Category 2 - The construction of rules and authority and the performance of marital and parental roles in couples with a child with ASD”, addressed the difficulties faced by couples with a child with the condition in relation to the experience of conjugality and parenting. The arrival of a child with ASD, with all the symptomatology and peculiarities of this condition, makes parents even more focused on issues related to the child, causing a decline in conjugality, with no prospects for resuming; “Category 3 - Managing Couple and Child Time,” addressed time-related issues within the Family Life Cycle and discussed the synchronicity between individual and family time. It was possible to identify that the couple's time is compromised due to the slower developmental time of the child with ASD, impacting the parental pair, who starts to live overlaps of the Family Life Cycle stage; “Category 4 - The health team as a third element in the relationship”, addressed the relationship between the couple and the health team, responsible for the diagnosis, treatment and follow-up of the child with ASD. It was observed that health specialists are central figures in the lives of these families, working as one of the relationship's partners, playing a fundamental role in family decisions. The study contributed to demonstrate that the interviewed couples have an impact on their marital status, regarding the existence of a child with ASD. The burden of care and dependence on the health team affect the couple, especially the mother, who was indicated as the primary caregiver. No evidence has been shown in the forecast reports for resumption of marital investments, as parents are still unable to have a clear view of the development and future of their child with ASD.